(3QSGdI aj GdMbjbI hGdeLGRs - (3QeRj eMeOs
(3ChdgG (B:s
(3hHYO adeG GQJMdJ Edi eMdI NhGfOhHGTQJ ajgG Edi GdJOQjS TQM JdNjU GdeYGfj ddJaJGRGfj dYOI ef GdWdGH GdaGgejf abO SFd efG HYV efgG HjGf hLg VHW GdMbjbI hGdeLGR hZjQgGs
(3BNQgG (B:s
(3bGd GdJaJGRGfj UGMH GdJdNjU GdGfJbGd aj GdeLGR hGdcfGjI cdjgeG ef GdedRhe Edi GddGRe EP dG OdGdI ddGRe ef MjK gh dGRe Ydi GdedRhe EdG Ef EQGOI GdehVhY dg LGFRI aj GdcfGjI Ohf GdeLGRs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdHdGZIs